Pedagogy of community-engaged research - Turin, Tanvir C; Datta, Ranjan; Marshall, Zack (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Community-engaged research (CEnR) has emerged as a transformative approach to knowledge co-creation, challenging academic hierarchies through equitable partnerships between communities and researchers. While much attention has been devoted to CEnR methodologies and ethics, less focus has been placed on how to effectively teach and learn its principles and practices. This paper presents a conceptual framework for CEnR pedagogy, outlining its foundational components rather than a full implementation strategy. The framework includes three interconnected elements that move beyond transmissive teaching toward transformative, learner-centered education. The first, Foundational Principles, addresses the “why” of CEnR education, emphasising epistemic humility, critical consciousness, relational competence, and ethical accountability. The second, Design Strategies, translates these principles into curriculum through capacity bridging, experiential learning, cultural responsiveness, and sustainability planning. The third, Teaching–Learning Practices, operationalises the framework through participatory teaching, community-based engagement, applied projects, reflexive practices, and contextual placement. Preparing researchers for authentic community engagement requires more than technical skills. It calls for critical reflexivity and relational accountability. We also acknowledge practical challenges, including institutional constraints and the risk of “lite pedagogy” that superficially incorporates CEnR principles without promoting genuine transformation. Safeguards include structured mentorship, reflective assessments, and co-teaching arrangements that center community voices. This conceptual pedagogical model supports learners in embodying CEnR’s core values while developing technical competencies, thereby strengthening both the integrity and societal relevance of community-engaged research. While the framework outlines strategies and methods conceptually, empirical testing, co-designed curricula, and evaluative metrics are future work that will require thoughtful investigation.